Pengaruh Persepsi Nilai, Persepsi Risiko, dan Persepsi Kegunaan terhadap Niat Pembelian Produk Ramah Lingkungan - Erik, Erik; Widyastuti, Liza Yudhita; Wijaya, Redo Tridinata; Simanjuntak, Dewi Fransiska (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study aims to investigate the impact of Perceived Value, Perceived Risk, and Perceived Usefulness on Green Purchase Intention. A quantitative approach was employed in this research. The population consisted of 581 potential users of electric motorcycles. The measurement instruments used in this study included the Green Purchase Intention scale adapted from Chen & Chang (2012), and the Perceived Risk, Perceived Value, and Perceived Usefulness scales adapted from Wu et al. (2014). Data analysis was conducted using Structural Equation Modeling (SEM) with the SmartPLS application. The results of the study indicate that Perceived Value has a P-value of 0.000, Perceived Risk has a P-value of 0.009, and Perceived Usefulness has a P-value of 0.000. Generally, Perceived Value, Perceived Risk, and Perceived Usefulness have a significant influence on Green Purchase Intention, with Perceived Value emerging as the most dominant factor. Based on the goodness-of-fit analysis, the model yielded a value of 0.399, and the R-squared value was 0.620. These values suggest that the model has good predictive capability. The implications of this study highlight that enhancing Perceived Value, reducing Perceived Risk, and increasing Perceived Usefulness can significantly improve Green Purchase Intention.